Metal-Free, One-Pot Synthesis of Allylic and Benzylic Esters via Decarboxylation and C–H Bond Activation - Mo, Hanjie; Chen, Dingben; Xu, Lingzhen; Chen, Di; Pan, Fuyou; Yang, Jianguo (Synthesis, 2015)
A tetrabutylammonium iodide catalyzed method has been developed for the one-pot synthesis of allylic and benzylic esters from α-oxo carboxylic acids and alkenes/alkylbenzenes via decarboxylation and C–H bond activation. Various allylic and benzylic esters were obtained in good yield.
Keywords: metal free; one-pot synthesis; decarboxylation; C–H bond activation; tetrabutylammonium iodide catalysis